The passion of Dolssa : a novel - Berry, Julie, 1974- (2016)
In mid-thirteenth century Provence, Dolssa de Stigata is a fervently religious girl who feels the call to preach, condemned by the Inquisition as an "unnatural woman," and hunted by the Dominican Friar Lucien who fears a resurgence of the Albigensian heresy; Botille is a matchmaker trying to protect her sisters from being branded as gypsies or witches--but when she finds the hunted Dolssa dying on a hillside, she feels compelled to protect her, a decision that may cost her everything.
Includes bibliographical references.
Ages 14-17
Keywords: Albigenses -- Juvenile fiction; Inquisition -- France -- Provence -- Juvenile fiction; Christian heresies -- Juvenile fiction; Faith -- Juvenile fiction; Albigenses -- Fiction; Inquisition -- Fiction; Christian heresies -- Fiction; Faith -- Fiction; Provence (France) -- History -- 13th century -- Juvenile fiction; France -- History -- Louis IX, 1226-1270 -- Juvenile fiction; Provence (France) -- History -- 13th century -- Fiction; France -- History -- Louis IX, 1226-1270 -- Fiction; Historical fiction